2016
DOI: 10.4103/0019-5049.183395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidural clonidine on characteristics of spinal anaesthesia in patients undergoing gynaecological surgeries: A clinical study

Abstract: Background and Aims:Combined spinal–epidural (CSE) anaesthesia is being increasingly used for effective post-operative analgesia. This study was designed to evaluate the effect of epidural clonidine on characteristics of spinal anaesthesia for gynaecological surgeries.Methods:This was a prospective randomised, double-blind, controlled study involving sixty patients belonging to American Society of Anesthesiologists Physical Status I and II who underwent gynaecological surgeries were randomly divided into cloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…In a study similar to ours, authors showed similar hemodynamic stability, significantly faster onset of motor and sensory block, and prolonged duration of analgesia using clonidine 150 mcg as a sole epidural adjuvant in an SAB with 3 cc hyperbaric bupivacaine. [ 4 ] This is in agreement with our study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In a study similar to ours, authors showed similar hemodynamic stability, significantly faster onset of motor and sensory block, and prolonged duration of analgesia using clonidine 150 mcg as a sole epidural adjuvant in an SAB with 3 cc hyperbaric bupivacaine. [ 4 ] This is in agreement with our study.…”
Section: Discussionsupporting
confidence: 94%
“…[ 3 ] Duration of analgesia was also prolonged with epidural clonidine as noted by other authors. [ 4 9 10 ] Although our study used only clonidine epidurally, it too showed the same findings.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Clonidine, alpha 2 adrenoreceptor agonist, has been very commonly used as an adjuvant with LA for epidural anesthesia,[ 8 9 ] peripheral nerve blocks,[ 6 10 ] abdominal plane block,[ 11 12 ] and local infiltration. [ 13 ] Clonidine acts by binding to presynaptic C fiber and post synaptic dorsal horn neurons and shows analgesics action by depressing the release of c-fibers, transmitter, and hyperpolarizing post synaptic dorsal horn; thus, significantly prolonging the sensory and motor block.…”
Section: Discussionmentioning
confidence: 99%